Four new species of Chinaia Bruner & Metcalf (Hemiptera: Cicadellidae: Neocoelidiinae) from the Neotropical Region - Marques, Ana Paula Coelho; Ale-Rocha, Rosaly (Zootaxa, 2016)
Four new species of Chinaia Bruner & Metcalf, Chinaia bicornis sp. nov., Chinaia longicauda sp. nov., Chinaia modesta sp. nov., and Chinaia peruviana sp. nov. are described and illustrated. The new species can be distinguished from the other species of the genus by characters of the male genitalia, especially the morphology of the pygofer and aedeagus. A generic diagnosis and a complete description, together with illustrations and pictures of the new species, are provided.